Effect of nano-size on magnetostriction of BiFeO3 and exceptional magnetoelectric coupling properties of BiFeO3_P(VDF-TrFE) polymer composite films for magnetic field sensor application. (1st April 2023) - Pradhan, Sonali; Deshmukh, Pratik; Kambale, Rahul C; Darvade, Tulshidas C; Satapathy, S; Majumder, Shovan K
Abstract: The existence of magnetostriction in bulk BiFeO3 is still a matter of investigation and it is also an issue to investigate the magnetostriction effect in nano BiFeO3 . Present work demonstrates the existence of magnetostrictive strain in superparamagnetic (SPM) BiFeO3 nanoparticles at room temperature and the magnetoelectric (ME) coupling properties in composite form with P(VDF-TrFE). Despite few reports on the magnetostriction effect in bulk BiFeO3 evidenced by the indirect method, the direct method (strain gauge) was employed in this work to examine the magnetostriction of SPM BiFeO3 . In addition, a high ME coupling coefficient was observed by the lock-in technique for optimized BiFeO3 _P(VDF-TrFE) nanocomposite film. These nanocomposite films also exhibit room-temperature multiferroic properties. These results provide aspects of material with immense potential for practical applications in spintronics and magneto-electronics applications. We report a ME sensor using SPM BiFeO3 _P(VDF-TrFE) nanocomposite film for detection of ac magnetic field.